PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT, DAN KUALITAS AUDIT TERHADAP AUDIT DELAY - Dela Puspita; Hari Stiawan (Asosiasi Dosen Muda Indonesia, 2026)
Audit delay, is a crucial problem in the business world because it can affect investor confidence and hinder market efficiency. The study aims to examine the influence of institutional ownership, audit committee, and audit quality on delay audit in industrial companies, listed on the Indonesia Stock Exchange from 2020-2024. The data source used in this study is secondary data in the form of the published financial statements of the company. The population in the research is all industrial companies, listed on the Indonesia Stock Exchange (BEI) period 2020-2024. The sample determination of this study using purposive sampling method and obtained sampling of 17 sample from 17 companies. The analysis method used in this study is the multi-linear regression method. The results of this study showed that partially institutional ownership had no effect on delay audits, the audit committee was influential but negative on delay audits, and the audit quality had no effect but negative on delay audits. Simultaneously demonstrates institutional ownership, audit committees and audit quality have a significant effect on delay audits.